Avian Paramyxoviruses: Detection by Transmission Electron Microscopy Techniques - Catroxo,M. H. B (Sociedad Chilena de Anatomía, 2012)
Diseases caused by avian paramyxovirus (APMV) occur in commercial, captive and wild birds worldwide, demonstrating the significant economic and ecological importance of these agents. Paramyxoviruses belong to the Paramyxoviridae family, Paramyxovirinae subfamily and Avulavirus genus. During the period 2000 to 2011, stool and small intestine samples of 1647 birds species were sent to the Laboratory of Electron Microscopy, Biological Institute of São Paulo, Brazil, for diagnosis of viral agents. The samples were processed by negative staining (rapid preparation) and resin embedding techniques. Under the transmission electron microscope by negative staining technique, in 294 (17.8%) samples of 1647 were visualized paramyxovirus particles pleomorphic, roughly spherical or filamentous, measuring 100 to 500 nm of diameter containing an envelope covered with spikes and characteristic helical herring-bone-like nucleocapsid measuring 15 to 20 nm in diameter. Ultrathin sections of the small intestine fragments revealed the presence of amorphous granular intracytoplasmic inclusions surrounded by membrane and containing viral nucleocapsid measuring 10-14 nm in diameter. Immature particles budding from cell membranes, pleomorphic, spherical and tubular particles containing viral nucleocapsid strands, and the complete particles measured up to 170 nm in diameter were seen in the cytoplasm. Intranuclear inclusions containing viral nucleocapsid were also visualized. Nuclei showed a marginalized chromatin.